Necessity of life-long follow-up after surgery for coarctation of the aorta: a case series of very late false aneurysm formation. Issue 2 (16th February 2022) - Somers, Tim; Nies, Hedwig M J M; van Kimmenade, Roland R J; Bosboom, Dennis G H; Geuzebroek, Guillaume S C; Morshuis, Wim J
Abstract: Background: Coarctation of the aorta accounts for 5–7% of congenital defects of the heart and great vessels. It requires treatment in the form of open surgical or percutaneous repair. Common long-term complications include re-stenosis and aneurysm formation. The formation of a false aneurysm is a complication with a significant morbidity and mortality. Case summary: We reviewed six cases of late false aneurysm after repair of a coarctation of the aorta. Our six cases developed a false aneurysm after an open surgical repair of a coarctation more than 30 years after initial surgical repair. All aneurysms were located at the aortic repair site. Discussion: The symptoms or risk factors in the described cases are not uniform and are difficult to include in a general follow-up protocol. Guidelines recommend frequent evaluation, but do not specify duration or intervals of imaging follow-up. Our cases support the necessity of life-long follow-up in patients with open aortic repairs irrespective of symptomatology.